Aspectos históricos da construção do Teatro das Bacabeiras: um recorte da memória da cena cultural - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The Bacabeiras Theatre is considered nowadays as the youngest public theatre of the northern area of the country, and characterizes itself by the modern architecture. Besides its short time of existence, the theatre doesn‘t possess a formal registration of its history. This way, this academic research has as its main goal making an analysis of the historic aspects of the Bacabeiras Theatre and its collaboration to the cultural development of Macapá/Ap. Looking forward to achieve the goals established, it was accomplished a research with qualitative kind of approach carrying out the field studies and interviews with six professionals and artists who had some kind of participation actively in the amapaense cultural scene, in the moment before the construction of the Bacabeiras theatre and after its opening. The mentioned study highlights that the construction of the theatre was finished in a time which most of the artists were amateurs, and the opening encourages those artists to search for professional empowerment and development, and still, stimulating the birth of more local theatre groups in comparison with the statistics before the theatre opening
Keywords: Teatro das Bacabeiras - Aspectos históricos; Memória; Teatro - Macapá (AP); Desenvolvimento cultural - Macapá (AP); CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO